An Exploratory Analysis of Factors Associated With Interest in Postpartum Intrauterine Device Uptake Among Pregnant Women and Couples in Kigali, Rwanda. (November 2019) - Da Costa, Vanessa; Ingabire, Rosine; Sinabamenye, Robertine; Karita, Etienne; Umutoni, Victoria; Hoagland, Alexandra; Allen, Susan; Mork, Ellen; Parker, Rachel; Mukamuyango, Jeannine; Haddad, Lisa; Nyombayire, Julien; et al.
Background: The desire to space or prevent future pregnancies is high among postpartum women in Rwanda. However, the use of long-acting reversible contraception (LARC), especially the highly effective and cost-effective copper intrauterine device (IUD), is very low, whereas the rates of unintended pregnancy are high. This study aims to identify factors associated with pregnant women's and couple's interest in receiving a postpartum intrauterine device (PPIUD) within 6 weeks after delivery. Methods: A total of 150 pregnant women or couples attending antenatal care (ANC) in Kigali, Rwanda participated in this cross-sectional study. After participating in a postpartum LARC counseling session, surveys assessed participants' demographics, pregnancy experiences and desires, and PPIUD knowledge, attitudes, practices, and interest. Multivariable logistic regression was used to model factors associated PPIUD interest within 6 weeks postpartum. Results: Although only 3% of women had ever used an IUD previously, 124 (83%) women were interested in receiving a PPIUD after counseling. Self-reporting physical side effects (adjusted odds ratio [aOR], 0.21; 95% confidence interval [CI], 0.06-0.75) and infection (aOR, 0.19; 95% CI, 0.04-0.85) as disadvantages to the IUD were significantly associated with no interest in receiving a PPIUD. Interest did not differ by male involvement. Conclusion: Recommendations to increase PPIUD uptake include educating pregnant women and couples about the method during ANC and addressing client myths and misconceptions about the IUD. This strategy allows pregnant women and couples to make informed decisions about their future contraception use, reduce unmet need for family planning, and reduce unintended pregnancy.